The Role of Good Corporate Governance to Fraud Prevention: An analysis based on the Fraud Pentagon - Rohmatin, Binti Lailatur; Apriyanto, Gaguk; Zuhroh, Diana (Jurnal Keuangan dan Perbankan, 2021)
This study aims to analyze the relationship between the causes of fraud, good corporate governance, and fraud. This study is a descriptive study tested using logistic regression analysis. This study used 27 samples of banking companies from 44 banking companies during 2016-2019, so there were 108 observations. This analysis shows that competence and opportunity have a significant positive effect on fraud, but rationalization, pressure, and arrogance have no effect on fraud. This research also revealed that good corporate governance could minimize the influence of opportunity and rationalization on fraud, but good corporate governance strengthens the competence Impact on Fraud. Meanwhile, pressure and arrogance are not moderated by good corporate governance. DOI :  https://doi.org/10.26905/jkdp.v25i2.5554